Reviving a Legacy Citizen Science Project to Illuminate Shifts in Bird Phenology. (20th May 2012) - Zelt, Jessica; Courter, Jason; Arab, Ali; Johnson, Ron; Droege, Sam
Abstract : Climate change has been of high interest to both the scientific community and the public at large since the phenomenon was first suggested. Subsequently, and with growing evidence of its impending ramifications, numerous studies have attempted to illuminate climate change impacts on bird migration. Migration is a key event in the annual cycle in the reproductive success of birds, and changes in migration in response to climate may indicate that species populations are at risk. Previous studies report earlier arrival dates in response to climate change in many bird species, although specific mechanisms are often difficult to explain at broad spatial and temporal scales. Using a newly revived dataset of historical migration cards for over 870 species and spanning 90 years throughout North America, we are developing an historical baseline of bird arrival dates to compare with contemporary records. Here we chronicle the history and reemergence of the North American Bird Phenology Program. We present two case studies illustrating how data from this program has been used to model historical arrival dates of Ruby-Throated Hummingbird ( Archilochus colubris ) and Purple Martin ( Progne subis ) throughout eastern North America. Our results show the importance of considering spatial and temporal variability in understanding patterns of bird spring arrivals.